Photovoltaic glass with down-conversion and ultraviolet reflection functions and preparation method thereof

By applying a rare earth downconversion layer and an ultraviolet reflective layer on photovoltaic glass, the problems of energy loss and performance attenuation of high-efficiency photovoltaic cells under ultraviolet light irradiation are solved, and the effect of improving the energy utilization rate of photovoltaic modules and protecting the performance of battery is achieved.

CN119797772APending Publication Date: 2025-04-11SUZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411991566.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

High-efficiency photovoltaic cells have energy loss and performance attenuation under ultraviolet light, which affects their conversion efficiency and service life.

Method used

Using photovoltaic glass with a rare earth downconversion layer and an ultraviolet reflective layer, the rare earth downconversion layer converts ultraviolet light into visible light, and the ultraviolet reflects unabsorbed ultraviolet light to improve the energy utilization rate of photovoltaic modules and protect the battery.

Benefits of technology

It effectively improves the energy conversion efficiency of photovoltaic cells, reduces the damage to the cells by ultraviolet light, and extends the service life of the cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797772A_ABST
    Figure CN119797772A_ABST
Patent Text Reader

Abstract

The invention discloses photovoltaic glass with down-conversion and ultraviolet reflection functions and a preparation method thereof.The photovoltaic glass comprises a glass substrate, an ultraviolet reflection layer and a rare earth down-conversion layer, the ultraviolet reflection layer and the rare earth down-conversion layer are located on at least one side of the glass substrate, and the rare earth down-conversion layer and the ultraviolet reflection layer are distributed in the light irradiation direction; the ultraviolet reflecting layer is used for reflecting incident ultraviolet light, and the rare earth down-conversion layer is used for converting the ultraviolet light which is incident, reflected or scattered by the ultraviolet reflecting layer into visible light. The photovoltaic glass has down-conversion and ultraviolet reflection functions, can effectively improve the energy conversion efficiency of a photovoltaic cell and protect the cell, does not need to additionally introduce a new structure, and is simple in preparation process, low in cost and suitable for mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photovoltaic cells, and in particular relates to a photovoltaic glass with down-conversion and ultraviolet reflection functions and a preparation method thereof. Background Art

[0002] Photovoltaics has become the main technical approach to achieve the "dual carbon" goals worldwide. High photoelectric conversion efficiency and low manufacturing cost are the key to reducing the cost of electricity of crystalline silicon solar cells. Although the new high-efficiency battery technology has obvious advantages, as the battery efficiency gradually approaches the theoretical limit efficiency, there is limited room for further improvement in terms of technology and cost, and there are still key technical problems that have not been solved. Studies have shown that the ultraviolet attenuation phenomenon of high-efficiency N-type photovoltaic cells is particularly serious. In addition, ultraviolet light in the solar spectrum can not only destroy the performance of the battery, but also accelerate the aging of the component packaging materials, causing them to discolor, swell, and fall off, shortening the service life of the battery. Therefore, it is particularly important to avoid the performance degradation of high-efficiency photovoltaic components caused by ultraviolet radiation and make full use of their energy to further improve the conversion efficiency and stability of batteries and components.

[0003] Therefore, in view of the above technical problems, it is necessary to provide a photovoltaic glass with down-conversion and ultraviolet reflection functions and a preparation method thereof. Summary of the invention

[0004] The object of the present invention is to provide a photovoltaic glass with down-conversion and ultraviolet reflection functions and a preparation method thereof, so as to improve the ultraviolet energy utilization of photovoltaic modules and avoid ultraviolet attenuation.

[0005] In order to achieve the above purpose, the technical solution provided by an embodiment of the present invention is as follows:

[0006] A photovoltaic glass with down-conversion and ultraviolet reflection functions, the photovoltaic glass comprising a glass substrate, an ultraviolet reflection layer and a rare earth down-conversion layer located on at least one side of the glass substrate, the rare earth down-conversion layer and the ultraviolet reflection layer being distributed along the direction of light irradiation, the ultraviolet reflection layer being used to reflect incident ultraviolet light, the rare earth down-conversion layer being used to convert ultraviolet light incident, reflected or scattered by the ultraviolet reflection layer into visible light, the ultraviolet reflection layer containing any one or more oxides of aluminum, magnesium, cerium and silicon, the rare earth down-conversion layer containing any one or more rare earth down-conversion nanoparticles of lanthanum, cerium, praseodymium, neodymium, bismuth, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium and yttrium.

[0007] In one embodiment, the ultraviolet reflection layer is located on the backlight surface of the glass substrate, and the rare earth down conversion layer is located on the light receiving surface of the glass substrate; or,

[0008] The ultraviolet reflection layer and the rare earth down conversion layer are sequentially stacked on the light receiving surface of the glass substrate; or,

[0009] The rare earth down conversion layer and the ultraviolet reflection layer are sequentially stacked on the backlight surface of the glass substrate.

[0010] In one embodiment, the ultraviolet reflective layer includes one or more of an aluminum oxide layer, a magnesium oxide layer, a cerium dioxide layer, and a silicon dioxide layer; and / or,

[0011] The thickness of the glass substrate is 1.6 mm to 3.2 mm; and / or,

[0012] The thickness of the ultraviolet reflection layer is 20nm to 100nm; and / or,

[0013] The rare earth lower conversion layer has a thickness of 20nm to 200nm.

[0014] Another embodiment of the present invention provides a technical solution as follows:

[0015] A method for preparing photovoltaic glass with down-conversion and ultraviolet reflection functions, the preparation method comprising the following steps:

[0016] providing a glass substrate;

[0017] A rare earth down-conversion layer and an ultraviolet reflection layer distributed along the light irradiation direction are prepared on at least one side of the glass substrate;

[0018] The preparation of the ultraviolet reflective layer comprises: dissolving the ultraviolet reflective material, heating and stirring with a polyvinyl alcohol solution to obtain a gel containing the ultraviolet reflective material, depositing the gel containing the ultraviolet reflective material on a glass substrate or a rare earth lower conversion layer, and drying and sintering to form the ultraviolet reflective layer;

[0019] The preparation of the rare earth down conversion layer comprises: preparing a rare earth down conversion material and dispersing it in a glass coating solution to obtain a down conversion composite solution containing the rare earth down conversion material, depositing the down conversion composite solution on a glass substrate or an ultraviolet reflection layer, and drying and sintering to form a rare earth down conversion layer;

[0020] Among them, the ultraviolet reflective material includes any one or more oxides of aluminum, magnesium, cerium and silicon, and the rare earth down-conversion material includes any one or more rare earth ion compounds of lanthanum, cerium, praseodymium, neodymium, bismuth, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium and yttrium.

[0021] In one embodiment, preparing a gel containing ultraviolet reflective material comprises:

[0022] The ultraviolet reflective material is ground into powder and added into a saturated ammonium bisulfate solution, and allowed to react fully, and the filtrate is dried and recrystallized after filtering, and the crystals are crushed and further dried to obtain ammonium sulfate chloride crystals with metal ions;

[0023] Taking ammonium sulfate chloride crystals and dissolving them in water to obtain an ammonium sulfate chloride aqueous solution, stirring an ammonia aqueous solution at room temperature and gradually dropping it into the ammonium sulfate chloride aqueous solution to generate a precipitate, taking out the precipitate and washing it thoroughly with deionized water until it is neutral;

[0024] The precipitate is transferred to a reaction container and a hydrochloric acid solution is added, and the mixture is heated and stirred at 40° C. to 80° C. in a water bath. After sufficient reaction, a polyvinyl alcohol solution is added and stirred continuously to obtain a gel containing an ultraviolet reflective material.

[0025] In one embodiment, preparing the ultraviolet reflective layer further comprises:

[0026] The gel containing the ultraviolet reflective material is deposited on a glass substrate or a rare earth lower conversion layer, dried at a temperature of 70°C to 90°C, and sintered at a temperature of 500°C to 700°C to form an ultraviolet reflective layer, wherein the mass of the ultraviolet reflective material per mg of the gel is 0.13 mg to 0.17 mg, and the deposition area per mg of the gel is 3 cm 2 ~5cm 2 , the thickness of the ultraviolet reflection layer is 20nm~100nm.

[0027] In one embodiment, preparing a rare earth down-conversion material comprises:

[0028] A rare earth ion compound precursor solution is prepared by mixing the rare earth ion solution, ethylene glycol, citric acid and ammonium metavanadate, stirring the mixture evenly and then heating the mixture to react in an inert environment until the ammonium metavanadate and the rare earth ions react completely to obtain a rare earth ion compound precursor solution, which is then stored in an inert environment;

[0029] Synthesizing rare earth ion compound crystals, drying a rare earth ion compound precursor solution at 60°C to 120°C for 5h to 10h to obtain a gel containing the rare earth ion compound, transferring the gel to a reaction kettle, reacting and drying at 100°C to 200°C for 12h to 24h, and filtering to obtain rare earth ion compound crystals;

[0030] The rare earth ions in the rare earth ion solution are selected from any one or more of lanthanum, cerium, praseodymium, neodymium, bismuth, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium and yttrium.

[0031] In one embodiment, preparing the rare earth down-conversion material further comprises:

[0032] Synthesizing a multi-rare earth ion doped compound, adding rare earth ion compound crystals to rare earth ion oxide and grinding them uniformly, placing the obtained particles in a crucible, and calcining them in an air atmosphere at a temperature of 700° C. to 1000° C. for 2 h to 5 h to recrystallize the rare earth ion compound crystals, and obtaining a rare earth down-conversion material containing a multi-rare earth ion compound;

[0033] The rare earth ions in the rare earth ion oxide are selected from any one or more of lanthanum, cerium, praseodymium, neodymium, bismuth, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium and yttrium.

[0034] In one embodiment, preparing the rare earth down conversion layer further comprises:

[0035] The down-conversion composite solution containing the rare earth down-conversion material is deposited on a glass substrate or an ultraviolet reflective layer, dried at a temperature of 110° C. to 150° C., and sintered at a temperature of 500° C. to 900° C. to form a rare earth down-conversion layer, wherein the content of the rare earth down-conversion material in each mL of the down-conversion composite solution is 0.7 mg to 0.9 mg, and the deposition area of ​​each mL of the down-conversion composite solution is 10 cm 2 ~20cm 2 The thickness of the rare earth lower conversion layer is 50nm to 200nm.

[0036] In one embodiment, in the preparation method:

[0037] The ultraviolet reflection layer is formed on the backlight surface of the glass substrate, and the rare earth down conversion layer is formed on the light receiving surface of the glass substrate; or,

[0038] The ultraviolet reflection layer is formed on the light receiving surface of the glass substrate, and the rare earth down conversion layer is formed on the ultraviolet reflection layer; or,

[0039] The rare earth down conversion layer is formed on the backlight surface of the glass substrate, and the ultraviolet reflection layer is formed on the rare earth down conversion layer.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] The photovoltaic glass of the present invention has downward conversion and ultraviolet reflection functions, can effectively improve the energy conversion efficiency of photovoltaic cells and protect the cells, does not require the introduction of additional new structures, has a simple preparation process, low cost, and is suitable for mass production;

[0042] The rare earth down conversion layer has a high fluorescence quantum yield and can convert ultraviolet light into visible light at a high conversion rate. The ultraviolet reflection layer can reflect the ultraviolet light that has not been completely absorbed back to the rare earth down conversion layer for secondary conversion, which effectively protects the battery while greatly improving the energy conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the embodiments are briefly introduced below.

[0044] Figure 1 This is a schematic diagram of the structure of photovoltaic glass in one embodiment of the present invention;

[0045] Figure 2 This is a schematic diagram of the structure of photovoltaic glass in another embodiment of the present invention;

[0046] Figure 3 This is a schematic diagram of the structure of photovoltaic glass in another embodiment of the present invention;

[0047] Figure 4 This is a SEM image of the rare earth down-conversion material in Example 1 of the present invention;

[0048] Figure 5 This is a SEM image of the rare earth down-conversion material in Example 2 of the present invention;

[0049] Figure 6 This is a SEM image of the rare earth down-conversion material in Example 3 of the present invention. DETAILED DESCRIPTION

[0050] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0051] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" or "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" or "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0052] The invention discloses a photovoltaic glass with down-conversion and ultraviolet reflection functions, which comprises a glass substrate, an ultraviolet reflection layer and a rare earth down-conversion layer located on at least one side of the glass substrate, wherein the rare earth down-conversion layer and the ultraviolet reflection layer are distributed along the irradiation direction of light, the ultraviolet reflection layer is used for reflecting incident ultraviolet light, and the rare earth down-conversion layer is used for converting ultraviolet light incident, reflected or scattered by the ultraviolet reflection layer into visible light.

[0053] Ginseng Figure 1 As shown, the photovoltaic glass in one embodiment of the present invention includes a glass substrate 10, an ultraviolet reflection layer 20 and a rare earth down conversion layer 30, wherein the ultraviolet reflection layer 20 is located on the backlight surface of the glass substrate 10, and the rare earth down conversion layer 30 is located on the light receiving surface of the glass substrate 10.

[0054] Ginseng Figure 2 As shown, the photovoltaic glass in another embodiment of the present invention includes a glass substrate 10, an ultraviolet reflection layer 20 and a rare earth down conversion layer 30, wherein the ultraviolet reflection layer 20 and the rare earth down conversion layer 30 are sequentially stacked on the light receiving surface of the glass substrate 10.

[0055] Ginseng Figure 3 As shown, the photovoltaic glass in another embodiment of the present invention includes a glass substrate 10, an ultraviolet reflection layer 20 and a rare earth down conversion layer 30, wherein the rare earth down conversion layer 30 and the ultraviolet reflection layer 20 are sequentially stacked on the backlight surface of the glass substrate 10.

[0056] Preferably, in the present invention, the thickness of the glass substrate 10 is 1.6 mm to 3.2 mm, the thickness of the ultraviolet reflection layer 20 is 20 nm to 100 nm, and the thickness of the rare earth down conversion layer 30 is 20 nm to 200 nm.

[0057] Among them, the ultraviolet reflection layer 20 contains any one or more oxides of aluminum, magnesium, cerium and silicon, and the rare earth down conversion layer 30 contains any one or more rare earth down conversion nanoparticles of lanthanum, cerium, praseodymium, neodymium, bismuth, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium and yttrium.

[0058] The present invention also discloses a method for preparing photovoltaic glass with down-conversion and ultraviolet reflection functions, comprising the following steps:

[0059] providing a glass substrate;

[0060] A rare earth down-conversion layer and an ultraviolet reflection layer distributed along the light irradiation direction are prepared on at least one side of the glass substrate;

[0061] The preparation of the ultraviolet reflective layer comprises: dissolving the ultraviolet reflective material, heating and stirring the solution with a polyvinyl alcohol solution to obtain a gel containing the ultraviolet reflective material, and depositing the gel containing the ultraviolet reflective material on a glass substrate or a rare earth lower conversion layer, and drying and sintering to form the ultraviolet reflective layer;

[0062] The preparation of the rare earth down conversion layer comprises: preparing a rare earth down conversion material and dispersing it in a glass coating solution to obtain a down conversion composite solution containing the rare earth down conversion material, depositing the down conversion composite solution on a glass substrate or an ultraviolet reflection layer, and drying and sintering to form a rare earth down conversion layer;

[0063] Among them, the ultraviolet reflective material includes any one or more oxides of aluminum, magnesium, cerium and silicon, and the rare earth down-conversion material includes any one or more rare earth ion compounds of lanthanum, cerium, praseodymium, neodymium, bismuth, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium and yttrium.

[0064] Specifically, preparing the gel containing the ultraviolet reflective material comprises:

[0065] The ultraviolet reflective material is ground into powder and added into a saturated ammonium bisulfate solution, and allowed to react fully, and the filtrate is dried and recrystallized after filtering, and the crystals are crushed and further dried to obtain ammonium sulfate chloride crystals with metal ions;

[0066] Taking ammonium sulfate chloride crystals and dissolving them in water to obtain an ammonium sulfate chloride aqueous solution, stirring an ammonia aqueous solution at room temperature and gradually dropping it into the ammonium sulfate chloride aqueous solution to generate a precipitate, taking out the precipitate and washing it thoroughly with deionized water until it is neutral;

[0067] The precipitate is transferred to a reaction container and a hydrochloric acid solution is added, and the mixture is heated and stirred at 40° C. to 80° C. in a water bath. After sufficient reaction, a polyvinyl alcohol solution is added and stirred continuously to obtain a gel containing an ultraviolet reflective material.

[0068] Furthermore, preparing the ultraviolet reflection layer also includes:

[0069] The gel containing the ultraviolet reflective material is deposited on a glass substrate or a rare earth lower conversion layer, dried at a temperature of 70°C to 90°C, and sintered at a temperature of 500°C to 700°C to form an ultraviolet reflective layer, wherein the mass of the ultraviolet reflective material per mg of the gel is 0.13 mg to 0.17 mg, and the deposition area per mg of the gel is 3 cm 2 ~5cm 2 , the thickness of the ultraviolet reflection layer is 20nm~100nm.

[0070] Specifically, preparing the rare earth down-conversion material includes:

[0071] A rare earth ion compound precursor solution is prepared by mixing the rare earth ion solution, ethylene glycol, citric acid and ammonium metavanadate, stirring the mixture evenly and then heating the mixture to react in an inert environment until the ammonium metavanadate and the rare earth ions react completely to obtain a rare earth ion compound precursor solution, which is then stored in an inert environment;

[0072] Synthesizing rare earth ion compound crystals, drying a rare earth ion compound precursor solution at 60°C to 120°C for 5h to 10h to obtain a gel containing the rare earth ion compound, transferring the gel to a reaction kettle, reacting and drying at 100°C to 200°C for 12h to 24h, and filtering to obtain rare earth ion compound crystals;

[0073] The rare earth ions in the rare earth ion solution are selected from any one or more of lanthanum, cerium, praseodymium, neodymium, bismuth, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium and yttrium.

[0074] Preferably, preparing the rare earth down-conversion material further comprises:

[0075] Synthesizing a multi-rare earth ion doped compound, adding rare earth ion compound crystals to rare earth ion oxide and grinding them uniformly, placing the obtained particles in a crucible, and calcining them in an air atmosphere at a temperature of 700° C. to 1000° C. for 2 h to 5 h to recrystallize the rare earth ion compound crystals, and obtaining a rare earth down-conversion material containing a multi-rare earth ion compound;

[0076] The rare earth ions in the rare earth ion oxide are selected from any one or more of lanthanum, cerium, praseodymium, neodymium, bismuth, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium and yttrium.

[0077] Furthermore, preparing the rare earth down conversion layer also includes:

[0078] The down-conversion composite solution containing the rare earth down-conversion material is deposited on a glass substrate or an ultraviolet reflective layer, dried at a temperature of 110° C. to 150° C., and sintered at a temperature of 500° C. to 900° C. to form a rare earth down-conversion layer, wherein the content of the rare earth down-conversion material in each mL of the down-conversion composite solution is 0.7 mg to 0.9 mg, and the deposition area of ​​each mL of the down-conversion composite solution is 10 cm 2 ~20cm 2 The thickness of the rare earth lower conversion layer is 50nm to 200nm.

[0079] In the present invention, the deposition of the gel containing the ultraviolet reflective material and the down-conversion composite solution containing the rare earth down-conversion material can be carried out by any one of spin coating, scraping, pulling, 3D printing and physical vapor deposition.

[0080] Taking crystalline silicon photovoltaic modules as an example, the present invention utilizes the spectral conversion of rare earth down-conversion materials and the scattering characteristics of the ultraviolet reflective layer on the ultraviolet band, which can completely absorb and reflect the ultraviolet band that is poorly absorbed by crystalline silicon cells and will destroy the battery life, and convert it into visible light that is well absorbed by crystalline silicon cells, so that crystalline silicon modules can make more full use of the solar spectrum, improve the photoelectric conversion efficiency of crystalline silicon modules by about 2%, and at the same time reduce the ultraviolet attenuation rate by about 70%.

[0081] The present invention is further described below with reference to specific examples.

[0082] Embodiment 1:

[0083] The photovoltaic glass structure in this embodiment is as follows Figure 1As shown, the preparation method thereof comprises the following steps:

[0084] (1) A quartz glass substrate of 3 cm × 3 cm and 1 mm thick was used, cleaned by ultrasonic cleaning, and then subjected to alkaline polishing pretreatment on both sides as a substrate.

[0085] (2) Silicon oxide and ammonium bisulfate were weighed and prepared in a molar ratio of 1:4. The silicon oxide was ground into powder and added into a saturated ammonium bisulfate solution in five portions. The mixture was allowed to stand for 24 hours to allow for a full reaction to form solution A.

[0086] (3) Filter solution A, dry and recrystallize the filtrate three times, and finally crush the crystals and continue to dry to obtain ammonium sulfate chloride crystals with metal ions. Take 5g of ammonium sulfate chloride and dissolve it in water. Take 40mL of ammonia solution. Stir the aqueous solution at room temperature and gradually add the ammonium sulfate chloride aqueous solution dropwise to generate a precipitate. Take out the precipitate and wash it thoroughly with deionized water until it is neutral. Then transfer it quickly to a flask, add hydrochloric acid solution at a mass fraction of 1:2, and stir and heat at 60°C in a water bath. After sufficient reaction, add polyvinyl alcohol and continue stirring to obtain gel B.

[0087] (4) Cover the front side with the prepared quartz glass single-sided mask and immerse it in gel B, slowly lift it up and dry it in a 60% humidity environment for 24 hours, and finally move it to a tube furnace and heat it to 600°C and heat it for 3 hours to obtain quartz glass with a single-sided ultraviolet reflection layer.

[0088] (5) Take 2.8 g of yttrium oxide and 0.38 g of europium oxide and put them into 400 mL of deionized water. Add 50 mL of 68% nitric acid to dissolve them in a 60°C water bath with stirring. After the solution becomes clear and transparent, add citric acid and ammonium metavanadate in sequence. After the solution turns blue, add appropriate amount of ammonia water to adjust the pH to 2. Stir for 3 h in a 60°C water bath to form the final solution C.

[0089] (6) The prepared solution C is placed in a reaction kettle, heated to 200° C. and heated for 12 h to obtain a nanoscale (<100 nm) rare earth down-conversion particle precipitate, which is filtered and washed with deionized water until neutral and dried.

[0090] (7) Take 2 g of the dried down-conversion particles, add 0.1 g of bismuth oxide, place in a grinding mortar and grind evenly, put the ground powder in a crucible, and calcine at 800° C. for 4 h in a tube furnace under air atmosphere to obtain multi-rare earth ion-doped down-conversion particles.

[0091] (8) Take 4 mL of the glass coating solution and dilute it in 50 mL of ethanol solution. Then weigh 0.5 g of the nano rare earth down-conversion particles in step (7) and stir and mix them to obtain solution D.

[0092] (9) Using a pipette, take an appropriate amount of solution D and coat it on the other side of the quartz glass in step (3), then place it in a high-temperature furnace and calcine it at 710° C. for 110 seconds to finally obtain a photovoltaic glass with dual functions of down-conversion and ultraviolet reflection.

[0093] Comparative Example 1:

[0094] The photovoltaic glass in this comparative example is a quartz glass sheet. Specifically:

[0095] A quartz glass original sheet with a size of 3 cm×3 cm and a thickness of 1 mm was used, which was cleaned by ultrasonic cleaning and then pre-treated by alkaline polishing on both sides.

[0096] Comparative Example 2:

[0097] The photovoltaic glass in this comparative example only comprises an ultraviolet reflection layer, and its preparation method comprises the following steps:

[0098] (1) A quartz glass substrate of 3 cm × 3 cm and 1 mm thick was used, cleaned by ultrasonic cleaning, and then subjected to alkaline polishing pretreatment on both sides as a substrate.

[0099] (2) Silicon oxide and ammonium bisulfate were weighed and prepared in a molar ratio of 1:4. The silicon oxide was ground into powder and added into a saturated ammonium bisulfate solution in five portions. The mixture was allowed to stand for 24 hours to allow for a full reaction to form solution A.

[0100] (3) Filter solution A, dry and recrystallize the filtrate three times, and finally crush the crystals and continue to dry to obtain ammonium sulfate chloride crystals with metal ions. Take 5g of ammonium sulfate chloride and dissolve it in water. Take 40mL of ammonia solution. Stir the aqueous solution at room temperature and gradually add the ammonium sulfate chloride aqueous solution dropwise to generate a precipitate. Take out the precipitate and wash it thoroughly with deionized water until it is neutral. Then transfer it quickly to a flask, add hydrochloric acid solution at a mass fraction of 1:2, and stir and heat at 60°C in a water bath. After sufficient reaction, add polyvinyl alcohol and continue stirring to obtain gel B.

[0101] (4) Cover the front side with the prepared quartz glass single-sided mask and immerse it in gel B, slowly lift it up and dry it in a 60% humidity environment for 24 hours, and finally move it to a tube furnace and heat it to 600°C and heat it for 3 hours to obtain quartz glass with a single-sided ultraviolet reflection layer.

[0102] Comparative Example 3:

[0103] The photovoltaic glass in this comparative example only comprises a rare earth down-conversion layer, and its preparation method comprises the following steps:

[0104] (1) A quartz glass substrate of 3 cm × 3 cm and 1 mm thick was used, cleaned by ultrasonic cleaning, and then subjected to alkaline polishing pretreatment on both sides as a substrate.

[0105] (2) Take 2.8 g of yttrium oxide and 0.38 g of europium oxide and put them into 400 mL of deionized water. Add 50 mL of 68% nitric acid to dissolve them in a 60°C water bath with stirring. After the solution becomes clear and transparent, add citric acid and ammonium metavanadate in sequence. After the solution turns blue, add appropriate amount of ammonia water to adjust the pH to 2. Stir for 3 h in a 60°C water bath to form the final solution C.

[0106] (3) The prepared solution C is placed in a reaction kettle, heated to 200° C. and heated for 12 h to obtain a nanoscale (<100 nm) rare earth down-conversion particle precipitate, which is filtered and washed with deionized water until neutral and dried.

[0107] (4) Take 2 g of the dried down-conversion particles, add 0.1 g of bismuth oxide, and place them in a grinding mortar for uniform grinding. Among them, 2 g of the down-conversion particles are mainly composed of yttrium oxide and doped with europium ions. The molar ratio of yttrium ions to rare earth europium ions is 97:3, the mass ratio is 95:5, and the molar content of yttrium oxide is 97%. The ground powder is placed in a crucible and calcined at 800°C in an air atmosphere in a tubular furnace for 4 hours to obtain down-conversion particles doped with multiple rare earth ions.

[0108] (5) Take 4 mL of the glass coating solution and dilute it in 50 mL of ethanol solution, then weigh 0.5 g of the nano rare earth down-conversion particles in step (7) and stir and mix them to obtain solution D.

[0109] (6) Using a pipette, take an appropriate amount of solution D and coat it on one side of the quartz glass in step 1, then place it in a high-temperature furnace and calcine it at 710° C. for 110 seconds to finally obtain photovoltaic glass with down-conversion function.

[0110] The photovoltaic glass in Example 1 and Comparative Examples 1 to 3 were subjected to comparative test on the cell conversion efficiency. The test results are shown in Table 1. 2 ), the energy conversion efficiency of the crystalline silicon battery assembly encapsulated by the photovoltaic glass in Comparative Example 1 is 20.62%, the energy conversion efficiency of the crystalline silicon battery assembly encapsulated by the photovoltaic glass with down-conversion function in Comparative Example 3 is 20.97%, the energy conversion efficiency of the crystalline silicon battery assembly encapsulated by the photovoltaic glass with UV reflection function in Comparative Example 2 is 20.49%, and the energy conversion efficiency of the crystalline silicon battery assembly encapsulated by the photovoltaic glass with dual functions of down-conversion and UV reflection in Example 1 is 21.08%. It can be seen that the opening voltage Voc, short-circuit current Isc, fill factor FF and battery efficiency Eff of the crystalline silicon battery encapsulated by the photovoltaic glass with dual functions of down-conversion and UV reflection are greatly improved compared with other comparative examples, and the improvement relative to the down-conversion glass comes from the fact that the UV reflection layer reflects the unabsorbed UV light to the down-conversion layer for further conversion.

[0111] Table 1: Comparison of conversion efficiency of crystalline silicon cells encapsulated in photovoltaic glass

[0112] Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 <![CDATA[V oc (V)]]> 0.71 0.71 0.71 0.71 <![CDATA[I sc (mA)]]> 681.62 675.48 670.09 678.59 Eff(%) 21.08 20.62 20.49 20.97 FF(%) 72.86 72.87 72.89 72.90

[0113] The photovoltaic glass in Example 1 and Comparative Examples 1 to 3 were subjected to comparative ultraviolet absorption test, and the test results are shown in Table 2. It can be seen that the photovoltaic glass in Example 1 can effectively block the incident ultraviolet band (280nm to 380nm) light without affecting the transmittance of the visible light band (380nm to 1100nm) light.

[0114] Table 2: Comparison of light transmittance of photovoltaic glass

[0115]

[0116]

[0117] Embodiment 2:

[0118] The photovoltaic glass structure in this embodiment is as follows Figure 1 As shown, the preparation method thereof comprises the following steps:

[0119] (1) A quartz glass substrate of 3 cm × 3 cm and 1 mm thick was used, cleaned by ultrasonic cleaning, and then subjected to alkaline polishing pretreatment on both sides as a substrate.

[0120] (2) Silicon oxide and ammonium bisulfate were weighed and prepared in a molar ratio of 1:4. The silicon oxide was ground into powder and added into a saturated ammonium bisulfate solution in five portions. The mixture was allowed to stand for 24 hours to allow for a full reaction to form solution A.

[0121] (3) Filter solution A, dry and recrystallize the filtrate three times, and finally crush the crystals and continue to dry to obtain ammonium sulfate chloride crystals with metal ions. Take 5g of ammonium sulfate chloride and dissolve it in water. Take 40mL of ammonia solution. Stir the aqueous solution at room temperature and gradually add the ammonium sulfate chloride aqueous solution dropwise to generate a precipitate. Take out the precipitate and wash it thoroughly with deionized water until it is neutral. Then transfer it quickly to a flask, add hydrochloric acid solution at a mass fraction of 1:2, and stir and heat at 60°C in a water bath. After sufficient reaction, add polyvinyl alcohol and continue stirring to obtain gel B.

[0122] (4) Cover the front side with the prepared quartz glass single-sided mask and immerse it in gel B, slowly lift it up and dry it in a 60% humidity environment for 24 hours, and finally move it to a tube furnace and heat it to 600°C and heat it for 3 hours to obtain quartz glass with a single-sided ultraviolet reflection layer.

[0123] (5) 1.834 g of yttrium oxide, 0.166 g of europium oxide, and 0.1 g of bismuth oxide were placed in 400 mL of deionized water, and 50 mL of 68% nitric acid was added to dissolve the mixture in a 60°C water bath with stirring. After the mixture became clear, citric acid and ammonium metavanadate were added in sequence. After the reaction was fully completed, an appropriate amount of ammonia water was added to adjust the pH to 2. The mixture was stirred in a 60°C water bath for 3 h to form a final solution E.

[0124] (6) The prepared solution E is placed in a reaction kettle, heated to 200° C. and heated for 12 h to obtain a nanoscale (<100 nm) rare earth down-conversion particle precipitate, which is filtered and washed with deionized water until neutral and dried.

[0125] (7) Take 4 mL of the glass coating solution and dilute it in 50 mL of ethanol solution. Then weigh 0.5 g of the nano rare earth down-conversion particles in step (6) and stir and mix them to obtain solution F.

[0126] (8) Using a pipette, take an appropriate amount of solution F and coat it on the other side of the quartz glass in step (3), then place it in a high-temperature furnace and calcine it at 710° C. for 110 seconds to finally obtain a photovoltaic glass with dual functions of down-conversion and ultraviolet reflection.

[0127] Embodiment 3:

[0128] The photovoltaic glass structure in this embodiment is as follows Figure 1 As shown, the preparation method thereof comprises the following steps:

[0129] (1) A quartz glass substrate of 3 cm × 3 cm and 1 mm thick was used, cleaned by ultrasonic cleaning, and then subjected to alkaline polishing pretreatment on both sides as a substrate.

[0130] (2) Silicon oxide and ammonium bisulfate were weighed and prepared in a molar ratio of 1:4. The silicon oxide was ground into powder and added into a saturated ammonium bisulfate solution in five portions. The mixture was allowed to stand for 24 hours to allow for a full reaction to form solution A.

[0131] (3) Filter solution A, dry and recrystallize the filtrate three times, and finally crush the crystals and continue to dry to obtain ammonium sulfate chloride crystals with metal ions. Take 5g of ammonium sulfate chloride and dissolve it in water. Take 40mL of ammonia solution. Stir the aqueous solution at room temperature and gradually add the ammonium sulfate chloride aqueous solution dropwise to generate a precipitate. Take out the precipitate and wash it thoroughly with deionized water until it is neutral. Then transfer it quickly to a flask, add hydrochloric acid solution at a mass fraction of 1:2, and stir and heat at 60°C in a water bath. After sufficient reaction, add polyvinyl alcohol and continue stirring to obtain gel B.

[0132] (4) Cover the front side with the prepared quartz glass single-sided mask and immerse it in gel B, slowly lift it up and dry it in a 60% humidity environment for 24 hours, and finally move it to a tube furnace and heat it to 600°C and heat it for 3 hours to obtain quartz glass with a single-sided ultraviolet reflection layer.

[0133] (5) Take 1.834 g of yttrium oxide and 0.166 g of europium oxide and put them into 400 mL of deionized water. Add 50 mL of 68% nitric acid to dissolve them in a 60°C water bath with stirring. After the solution becomes clear and transparent, add citric acid and ammonium metavanadate in sequence. After the solution turns blue, add appropriate amount of ammonia water to adjust the pH to 2. Stir for 3 h in a 60°C water bath to form the final solution G.

[0134] (6) The prepared solution G is placed in a reaction kettle, heated to 200° C. and heated for 12 h to obtain nanoscale (<100 nm) rare earth down-conversion particle precipitates, which are filtered and washed with deionized water until neutral and dried.

[0135] (7) 4 mL of the glass coating solution was diluted in 50 mL of ethanol solution, and 0.5 g of the nano rare earth down-conversion particles in step (6) were weighed and stirred to obtain a solution H.

[0136] (8) Using a pipette, take an appropriate amount of solution H and coat it on the other side of the quartz glass in step (3), then place it in a high-temperature furnace and calcine it at 710° C. for 110 seconds to finally obtain a photovoltaic glass with dual functions of down-conversion and ultraviolet reflection.

[0137] The difference between Example 1 and Examples 2 and 3 is that Example 1 adopts a two-step method to dope two rare earth ions, namely steps (5) and (7) in Example 1, Example 2 adopts a one-step method to dope two rare earth ions, namely step (5) in Example 2, and Example 3 adopts a one-step method to dope one rare earth ion, namely step (5) in Example 3. Figures 4 to 6 They are SEM images of the rare earth down-conversion materials in Examples 1 to 3 respectively. It can be seen that the rare earth down-conversion material prepared by doping with two rare earth ions using a two-step method in Example 1 has a more uniform surface morphology, is closer to a spherical shape, and has better crystallinity.

[0138] In addition, the fluorescence quantum yields of the rare earth down-conversion materials in Examples 1 to 3 are shown in Table 3. It can be seen that the rare earth down-conversion material prepared by doping two rare earth ions using a two-step method in Example 1 has the highest fluorescence performance, and the fluorescence quantum yield PLQY reaches 78.35%.

[0139] Table 3: Comparison of fluorescence quantum yields of rare earth down-conversion materials

[0140] Example 1 Example 2 Example 3 PLQY(%) 78.35 67.21 47.9

[0141] The photovoltaic glass in Comparative Example 1 and Examples 1 to 3 were subjected to comparative test on the cell conversion efficiency. The test results are shown in Table 4. 2 ) under the standard test conditions, the energy conversion efficiency of the crystalline silicon battery assembly encapsulated by photovoltaic glass in Example 1 is the highest, which is 21.14%.

[0142] Table 4: Comparison of conversion efficiency of crystalline silicon cells encapsulated in photovoltaic glass

[0143] Comparative Example 1 Example 1 Example 2 Example 3 <![CDATA[V oc (V)]]> 0.71 0.71 0.71 0.71 <![CDATA[I sc (mA)]]> 675.48 682.95 673.27 671.17 Eff(%) 20.62 21.14 20.58 20.52 FF(%) 72.87 72.88 72.88 72.88

[0144] The photovoltaic glasses in comparative example 1 and examples 1 to 3 were subjected to comparative ultraviolet absorption rate measurement, and the test results are shown in Table 5. It can be seen that the photovoltaic glasses in examples 1 to 3 can effectively block the incident ultraviolet band (280nm to 380nm) light without affecting the transmittance of the visible light band (380nm to 1100nm), but the photovoltaic glass in example 1 has the highest blocking efficiency in the ultraviolet band and the lowest transmittance.

[0145] Table 5: Comparison of light transmittance of photovoltaic glass

[0146]

[0147] Embodiment 4:

[0148] The photovoltaic glass structure in this embodiment is as follows Figure 2 As shown, the preparation of the ultraviolet reflection layer 20 and the rare earth down conversion layer 30 is similar to that in Example 1. The rare earth down conversion material is doped with two rare earth ions using a two-step method, which will not be described in detail here.

[0149] Embodiment 5:

[0150] The photovoltaic glass structure in this embodiment is as follows Figure 2 As shown, the preparation of the ultraviolet reflection layer 20 and the rare earth down conversion layer 30 is similar to that of Example 2. The rare earth down conversion material is doped with two rare earth ions using a one-step method, which will not be described in detail here.

[0151] Embodiment 6:

[0152] The photovoltaic glass structure in this embodiment is as follows Figure 2 As shown, the preparation of the ultraviolet reflection layer 20 and the rare earth down conversion layer 30 is similar to that in Example 3. The rare earth down conversion material is doped with a rare earth ion in a one-step method, which will not be described in detail here.

[0153] The photovoltaic glass in Comparative Example 1 and Examples 4 to 6 were subjected to comparative test on the cell conversion efficiency. The test results are shown in Table 6. 2 ), the energy conversion efficiency of the crystalline silicon battery assembly encapsulated by photovoltaic glass in Example 4 is the highest, which is 21.08%.

[0154] Table 6: Comparison of conversion efficiency of crystalline silicon cells encapsulated in photovoltaic glass

[0155] Comparative Example 1 Example 4 Example 5 Example 6 <![CDATA[V oc (V)]]> 0.71 0.71 0.71 0.71 <![CDATA[I sc (mA)]]> 675.48 681.62 672.35 670.08 Eff(%) 20.62 21.08 20.54 20.49 FF(%) 72.87 72.86 72.87 72.87

[0156] The photovoltaic glasses in comparative example 1 and examples 4 to 6 were subjected to comparative ultraviolet absorption rate measurement, and the test results are shown in Table 7. It can be seen that the photovoltaic glasses in examples 4 to 6 can effectively block the incident ultraviolet band (280nm to 380nm) light without affecting the transmittance of the visible light band (380nm to 1100nm), but the photovoltaic glass in example 4 has the highest blocking efficiency in the ultraviolet band and the lowest transmittance.

[0157] Table 7: Comparison of light transmittance of photovoltaic glass

[0158]

[0159] Likewise, Figure 3 The photovoltaic glass in has similar effects, which will not be described in detail here.

[0160] The down-conversion material in the present invention is a luminescent material that can convert high-energy short-wavelength photons into medium and low-energy photons. It is combined with a battery to not only improve the battery short-wave response, reduce lattice heat loss, but also reduce the radiation effect of ultraviolet light on the battery. The traditional rare earth down-conversion material has a low absorption cross section and cannot completely convert ultraviolet light. In Examples 1 and 4 of the present invention, different rare earth ions are introduced in the hydrothermal method and recrystallization process to regulate the matrix lattice and expand the luminescent center, so that the down-conversion material has a higher fluorescence quantum yield, and a smaller particle size can provide higher optical transmittance. At the same time, the introduction of an ultraviolet reflection layer can not only reflect the ultraviolet light that is not completely absorbed by the down-conversion material, but also protect the battery from damage by high-energy ultraviolet light while improving the light utilization rate. Therefore, the present invention is expected to further improve the power of photovoltaic modules, and can effectively improve the anti-ultraviolet attenuation performance of batteries and modules, which is an ideal strategy for high-efficiency photovoltaic modules to improve ultraviolet energy utilization and avoid ultraviolet attenuation.

[0161] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0162] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A photovoltaic glass with down-conversion and ultraviolet reflection functions, characterized in that: The photovoltaic glass comprises a glass substrate, an ultraviolet reflection layer and a rare earth down-conversion layer located on at least one side of the glass substrate, wherein the rare earth down-conversion layer and the ultraviolet reflection layer are distributed along the direction of light irradiation, the ultraviolet reflection layer is used to reflect incident ultraviolet light, and the rare earth down-conversion layer is used to convert ultraviolet light incident, reflected or scattered by the ultraviolet reflection layer into visible light, the ultraviolet reflection layer contains any one or more oxides of aluminum, magnesium, cerium and silicon, and the rare earth down-conversion layer contains any one or more rare earth down-conversion nanoparticles of lanthanum, cerium, praseodymium, neodymium, bismuth, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium and yttrium.

2. The photovoltaic glass with down-conversion and ultraviolet reflection functions according to claim 1, characterized in that: The ultraviolet reflection layer is located on the backlight surface of the glass substrate, and the rare earth down conversion layer is located on the light receiving surface of the glass substrate; or, The ultraviolet reflection layer and the rare earth down conversion layer are sequentially stacked on the light receiving surface of the glass substrate; or, The rare earth down conversion layer and the ultraviolet reflection layer are sequentially stacked on the backlight surface of the glass substrate.

3. The photovoltaic glass with down-conversion and ultraviolet reflection functions according to claim 1, characterized in that: The ultraviolet reflective layer includes one or more of an aluminum oxide layer, a magnesium oxide layer, a cerium dioxide layer, and a silicon dioxide layer; and / or, The thickness of the glass substrate is 1.6 mm to 3.2 mm; and / or, The thickness of the ultraviolet reflection layer is 20nm to 100nm; and / or, The rare earth lower conversion layer has a thickness of 20nm to 200nm.

4. A method for preparing photovoltaic glass with down-conversion and ultraviolet reflection functions, characterized in that: The preparation method comprises the following steps: providing a glass substrate; A rare earth down-conversion layer and an ultraviolet reflection layer distributed along the light irradiation direction are prepared on at least one side of the glass substrate; The preparation of the ultraviolet reflective layer comprises: dissolving the ultraviolet reflective material, heating and stirring with a polyvinyl alcohol solution to obtain a gel containing the ultraviolet reflective material, depositing the gel containing the ultraviolet reflective material on a glass substrate or a rare earth lower conversion layer, and drying and sintering to form the ultraviolet reflective layer; The preparation of the rare earth down conversion layer comprises: preparing a rare earth down conversion material and dispersing it in a glass coating solution to obtain a down conversion composite solution containing the rare earth down conversion material, depositing the down conversion composite solution on a glass substrate or an ultraviolet reflection layer, and drying and sintering to form a rare earth down conversion layer; Among them, the ultraviolet reflective material includes any one or more oxides of aluminum, magnesium, cerium and silicon, and the rare earth down-conversion material includes any one or more rare earth ion compounds of lanthanum, cerium, praseodymium, neodymium, bismuth, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium and yttrium.

5. The photovoltaic glass with down-conversion and ultraviolet reflection functions according to claim 4, characterized in that: The preparation of a gel containing a UV reflective material comprises: The ultraviolet reflective material is ground into powder and added into a saturated ammonium bisulfate solution, and allowed to react fully, and the filtrate is dried and recrystallized after filtering, and the crystals are crushed and further dried to obtain ammonium sulfate chloride crystals with metal ions; Taking ammonium sulfate chloride crystals and dissolving them in water to obtain an ammonium sulfate chloride aqueous solution, stirring an ammonia aqueous solution at room temperature and gradually dropping it into the ammonium sulfate chloride aqueous solution to generate a precipitate, taking out the precipitate and washing it thoroughly with deionized water until it is neutral; The precipitate is transferred to a reaction container and a hydrochloric acid solution is added, and the mixture is heated and stirred at 40° C. to 80° C. in a water bath. After sufficient reaction, a polyvinyl alcohol solution is added and stirred continuously to obtain a gel containing an ultraviolet reflective material.

6. The photovoltaic glass with down-conversion and ultraviolet reflection functions according to claim 5, characterized in that: The preparation of the ultraviolet reflective layer also includes: The gel containing the ultraviolet reflective material is deposited on a glass substrate or a rare earth lower conversion layer, dried at a temperature of 70°C to 90°C, and sintered at a temperature of 500°C to 700°C to form an ultraviolet reflective layer, wherein the mass of the ultraviolet reflective material per mg of the gel is 0.13 mg to 0.17 mg, and the deposition area per mg of the gel is 3 cm 2 ~5cm 2 , the thickness of the ultraviolet reflection layer is 20nm~100nm.

7. The photovoltaic glass with down-conversion and ultraviolet reflection functions according to claim 4, characterized in that: The preparation of rare earth down-conversion materials includes: A rare earth ion compound precursor solution is prepared by mixing the rare earth ion solution, ethylene glycol, citric acid and ammonium metavanadate, stirring the mixture evenly and then heating the mixture to react in an inert environment until the ammonium metavanadate and the rare earth ions react completely to obtain a rare earth ion compound precursor solution, which is then stored in an inert environment; Synthesizing rare earth ion compound crystals, drying a rare earth ion compound precursor solution at 60°C to 120°C for 5h to 10h to obtain a gel containing the rare earth ion compound, transferring the gel to a reaction kettle, reacting and drying at 100°C to 200°C for 12h to 24h, and filtering to obtain rare earth ion compound crystals; The rare earth ions in the rare earth ion solution are selected from any one or more of lanthanum, cerium, praseodymium, neodymium, bismuth, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium and yttrium.

8. The photovoltaic glass with down-conversion and ultraviolet reflection functions according to claim 7, characterized in that: The preparation of rare earth down-conversion materials also includes: Synthesizing a multi-rare earth ion doped compound, adding rare earth ion compound crystals to rare earth ion oxide and grinding them uniformly, placing the obtained particles in a crucible, and calcining them in an air atmosphere at a temperature of 700° C. to 1000° C. for 2 h to 5 h to recrystallize the rare earth ion compound crystals, and obtaining a rare earth down-conversion material containing a multi-rare earth ion compound; The rare earth ions in the rare earth ion oxide are selected from any one or more of lanthanum, cerium, praseodymium, neodymium, bismuth, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium and yttrium.

9. The photovoltaic glass with down-conversion and ultraviolet reflection functions according to claim 7 or 8, characterized in that: The preparation of the rare earth down conversion layer also includes: The down-conversion composite solution containing the rare earth down-conversion material is deposited on a glass substrate or an ultraviolet reflective layer, dried at a temperature of 110° C. to 150° C., and sintered at a temperature of 500° C. to 900° C. to form a rare earth down-conversion layer, wherein the content of the rare earth down-conversion material in each mL of the down-conversion composite solution is 0.7 mg to 0.9 mg, and the deposition area of ​​each mL of the down-conversion composite solution is 10 cm 2 ~20cm 2 The thickness of the rare earth lower conversion layer is 50nm to 200nm.

10. The photovoltaic glass with down-conversion and ultraviolet reflection functions according to claim 4, characterized in that: In the preparation method: The ultraviolet reflection layer is formed on the backlight surface of the glass substrate, and the rare earth down conversion layer is formed on the light receiving surface of the glass substrate; or, The ultraviolet reflection layer is formed on the light receiving surface of the glass substrate, and the rare earth down conversion layer is formed on the ultraviolet reflection layer; or, The rare earth down conversion layer is formed on the backlight surface of the glass substrate, and the ultraviolet reflection layer is formed on the rare earth down conversion layer.

Citation Information

Patent Citations

  • Solar cell with high photoelectric conversion efficiency

    CN202651175U